ANALYSIS OF THE INFLUENCE OF FINANCIAL LITERACY AND LIFESTYLE ON THE PERSONAL FINANCIAL MANAGEMENT OF BOJONEGORO UNIVERSITY STUDENTS - Reza Anggapratama; Dwi Irnawati; Kustaji Kustaji; Muhammad Rizqi Agustino; Fauzian Noor; Shofie Shalzabilla Meta Firanka (Economic Education Faculty of Economics and Business Universitas PGRI Sumatera Barat, 2025)
This study aims to determine the effect of financial literacy and lifestyle on the personal financial management of Bojonegoro University students, given the low level of financial literacy in Indonesia and the importance of adequate understanding of finance to support economic growth and financial well-being. This study also aims to determine whether financial literacy and lifestyle jointly affect the personal financial management of these students. The research method used is a mixed-method approach using a sample of 100 Bojonegoro University students. Data were collected through the use of questionnaires and interviews. Quantitative data were analyzed using validity, reliability, normality, multicollinearity, heteroscedasticity, t-test, F test, and R test with the help of the SPSS version 21 application. The results showed that financial literacy had a significant effect on the personal financial management of Bojonegoro University students, while lifestyle had no significant effect. In addition, financial literacy and lifestyle together have a significant effect on the personal financial management of these students simultaneously. Financial literacy and lifestyle variables together contribute 34.92% to the personal financial management of Bojonegoro University students.